Childhood cancer survivorship: barriers and preferences. Issue Volume 12:Issue e5(2022) (11th November 2019) - Signorelli, Christina; Wakefield, Claire; McLoone, Jordana K; Fardell, Joanna; Jones, Janelle M; Turpin, Kate H; Emery, Jon; Michel, Gisela; Downie, Peter; Skeen, Jane E; Cohn, Richard
Abstract : Objective: Many survivors are disengaged from follow-up, mandating alternative models of survivorship-focused care for late effects surveillance. We explored survivors' barriers to accessing, and preferences for survivorship care. Methods: We invited Australian and New Zealand survivors of childhood cancer from three age groups: <16 years (represented by parents), 16–25 years (adolescent and young adults (AYAs)) and >25 years ('older survivors'). Participants completed questionnaires and optional interviews. Results: 633 survivors/parents completed questionnaires: 187 parents of young survivors (mean age: 12.4 years), 251 AYAs (mean age: 20.6 years) and 195 older survivors (mean age: 32.5 years). Quantitative data were complemented by 151 in-depth interviews. Most participants, across all age groups, preferred specialised follow-up (ie, involving oncologists, nurses or a multidisciplinary team; 86%–97%). Many (36%–58%) were unwilling to receive community-based follow-up. More parents (75%) than AYAs (58%) and older survivors (30%) were engaged in specialised follow-up. While follow-up engagement was significantly lower in older survivors, survivors' prevalence of late effects increased. Of those attending a follow-up clinic, 34%–56% were satisfied with their care, compared with 14%–15% of those not receiving cancer-focused care (p<0.001). Commonly reported barriers included lack of awareness about follow-up availability (67%), followed by logistical (65%), care-related beliefs (59%) and financial reasons (57%). Older survivors (p<0.001), living outside major cities (p=0.008), and who were further from diagnosis (p=0.014) reported a higher number of barriers. Conclusions: Understanding patient-reported barriers, and tailoring care to survivors' follow-up preferences, may improve engagement with care and ensure that the survivorship needs of this population are met.